2018
DOI: 10.3390/ijerph15122814
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Education, Fertility, and Child Survival in Comoros

Abstract: Reduction in child mortality is a demographic progress of significant socioeconomic development relevance in Africa. This paper analyzed the effect of maternal education and fertility on child survival in the Islands of Comoros. The 2012 Demographic and Health Survey (DHS) data were used. A two-stage probit regression method was used for data analysis. The results showed that about 75% of the children’s mothers had given birth to between one and five children, while more than half did not have any form of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 73 publications
2
16
0
1
Order By: Relevance
“…knowledge, awareness) [13,25]. This protective effect of maternal education adjusted for more covariates than in the study at hand, was also reported in Ghana [30], and Comoros [31]. Some assumptions suggested in a study on the factors associated with U5MR in rural Ghana were: educated mothers are more likely to receive antenatal care [32] (though the gap seems to be closing over time [33]), and motherhood could be delayed, decreasing the total number of children [34].…”
Section: Resultssupporting
confidence: 71%
“…knowledge, awareness) [13,25]. This protective effect of maternal education adjusted for more covariates than in the study at hand, was also reported in Ghana [30], and Comoros [31]. Some assumptions suggested in a study on the factors associated with U5MR in rural Ghana were: educated mothers are more likely to receive antenatal care [32] (though the gap seems to be closing over time [33]), and motherhood could be delayed, decreasing the total number of children [34].…”
Section: Resultssupporting
confidence: 71%
“…Based on the results of previous studies above, the high fertility rate that occurs is of course not only caused by factors of marriage, use of contraceptives, deliberate abortion, and breastfeeding (Harrison, 2016;Glasier, 2019). Demographic, social, economic, and cultural factors affect fertility through proximate determinants that directly affect fertility rates (Davis and Blake, 1956;Oyekale, 2018). Therefore, it is important to carry out further analysis of trends or patterns of changes in determinants of fertility using data from the 2002/2003 and 2017 IDHS results in NTT Province, so as to get a picture of taking a more appropriate approach in reducing the fertility rate in this province.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of women's schooling was another indicator that proved to be a strong and consistent predictor of under-five mortality. The significant influence of maternal education on a child's health and survival is thus an important area of research 23 . Maternal education contributes to the mother's awareness of good health practices, in situations of the children's illness and availability of health services, so that it is considered a factor that positively affects the child's health.…”
Section: Discussionmentioning
confidence: 99%